Modeling of the Full-Scale Secondary Sedimentation Basin Using the GPS-X Model - Hasan, Safi A.; Nile, Basim K.; Faris, Ahmed M. (Salehan Institute of Higher Education, 2024)
The secondary sedimentation basin is being modeled in this study for the first time using the GPS-X model instead of the computational fluid dynamics (CFD) model. This study was conducted in the extended-aeration Al-Hur treatment plant that struggles with unstable sedimentation in its sedimentation tank. After collecting and entering the data into the GPS-X model, the model was calibrated and validated, and the results were statistically examined based on R and RMSE. To determine the efficiency of the sedimentation tank, the following scenarios were investigated: 1) testing the efficiency in removing pollutants; 2) conducting state point analysis (SPA); and 3) measuring the concentration of sludge in the layers of the sedimentation basin. Six factors were considered during the sensitivity analysis, namely sludge volume index (SIV), surface area, underflow rate (RAS), pumped flow (WAS), maximum settling velocity, and liquid temperature. The calibration and validation results were within the specified limits, and the secondary sedimentation basin demonstrated high efficiency in removing pollutants, with the analysis point (SPA) obtaining the highest MLSS concentration of 3000 mg/L. The sludge concentrations in the lower layers were 7000 mg/L, while those in the upper layer were 18 mg/L. These results suggest that a lower (100 ml/g) sludge volume index corresponds to a better sedimentation basin efficiency. Increasing the surface area of sedimentation basins can positively affect their efficiency, while increasing waste-activated sludge, maximum settling velocity, and liquid temperature may reduce pollutants and improve the sedimentation process. The GPS-X model is demonstrated as an excellent tool for understanding and predicting the work behavior of sedimentation basins, making this model particularly valuable for the management of sewage treatment plants. Doi: 10.28991/CEJ-2024-010-09-017 Full Text: PDF